2017
DOI: 10.3390/toxins9040137
|View full text |Cite
|
Sign up to set email alerts
|

An On-Site, Ultra-Sensitive, Quantitative Sensing Method for the Determination of Total Aflatoxin in Peanut and Rice Based on Quantum Dot Nanobeads Strip

Abstract: An on-site, ultra-sensitive, and quantitative sensing method was developed based on quantum dot nanobeads (QDNBs) and a test strip for the determination of total aflatoxins (AFTs) in rice and peanuts. The monoclonal antibody against AFT (mAbAFT) was homemade and labeled with QDNB. After the pre-coating of the AFT antigen on the test line (T line), the competitive immunoreactions were conducted between AFT and AFT antigen on the T line with QDNBs-mAbAFT. Under optimal conditions, this approach allowed a rapid r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…QDNBs–mAb conjugates were prepared by following previously published QDNBs antibody conjugation protocol [ 26 ]. Briefly, 3 mL of QDNBs solution was dispersed in 0.05 M MES (2-[N-morpholino]ethanesulfonicacid, pH 6.0) and activated with 12 mg of EDC and 18 mg of NHS at room temperature for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…QDNBs–mAb conjugates were prepared by following previously published QDNBs antibody conjugation protocol [ 26 ]. Briefly, 3 mL of QDNBs solution was dispersed in 0.05 M MES (2-[N-morpholino]ethanesulfonicacid, pH 6.0) and activated with 12 mg of EDC and 18 mg of NHS at room temperature for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Peeled almonds and peanuts showed a positive result at the cutoff level, whereas the unpeeled nuts showed a positive result slightly above the cutoff level in the test that was used. The work from Zhang et al analyzed the aflatoxins in peanuts and other commodities [22,23] and reported good recoveries when testing with different matrices such as nut samples.…”
Section: Matrix Effect Testingmentioning
confidence: 99%
“…70 Ouyang et al reported antibody-antigen interaction based detection of aflatoxin using quantum dot nanobeads with the LODs of 1.4 and 2.9 pg/mL for rice and peanut samples, respectively. 71 Other QD-based Immunochromatographic assays have been widely employed in the analysis of AFTs (mainly for AFB1). 72 Zearalenone (ZEA) also known as RAL and F-2 mycotoxin is a macrocyclic β-resorcyclic acid lactone and a nonesteroidalestrogenic mycotoxin produced by some Fusarium and Gibberella species.…”
Section: •3•2 Mycotoxinsmentioning
confidence: 99%